IKEA: capable food lid / Nur Aisyah Maslin - Maslin, Nur Aisyah (2022)
IKEA is a Swedish company which produce produce many types of products such as furniture, home textiles and kitchen appliances. In this company analysis, it is focussing on the food lid that is produced by the IKEA to be investigate, identified and analysed along with their current problems and come out with solutions. Based on SWOT analysis, the first problem regarding their product contains manufacturing defects. It happens when a product deviates from its intended design, regardless of how carefully the designer designed it, selected components, and over saw its construction. The next problem is the food lid only one size and hard to store. Aside from that, there are few solutions to that problems primarily are identified and corrected before they impact the general population with sufficient preventive maintenance. The next solution is to make the food lid foldable and add variation to the product. Product variations were designed to increase the consumer experience by allowing shoppers to look for and compare items that differ slightly from one another.